Genetic study of indirect inguinal hernia. Issue 3 (March 1994) - Gong, Y; Shao, C; Sun, Q; Chen, B; Jiang, Y; Guo, C; Wei, J; Guo, Y
Abstract : We performed a genetic analysis of 280 families with congenital indirect inguinal hernia ascertained in Shandong province. The multifactorial threshold model and segregation analysis were applied to these families to investigate the mode of inheritance of congenital indirect inguinal hernia. Our results indicate that congenital indirect inguinal hernia is not compatible with a multifactorial threshold model, and the frequent vertical transmission and high segregation ratio suggest autosomal dominant inheritance with incomplete penetrance and sex influence. Through further pedigree analysis of the multiple case families with at least two closely related affected members, we noted preferential paternal transmission of the disease gene, which might suggest the role of genomic imprinting in the aetiology of this condition.